Public Perception of Water Quality as a Planning Tool - Judge, R. M. (Arizona-Nevada Academy of Science, 1973)
From the Proceedings of the 1973 Meetings of the Arizona Section - American Water Resources Assn. and the Hydrology Section - Arizona Academy of Science - May 4-5, 1973, Tucson, Arizona